Integrasi Moral dan Etika dalam Pendidikan Agama Islam - Dwi Daryanto; Fetty Ernawati (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2024)
Islamic education must have an active role in maintaining the nation's generation that has morals and ethics and adheres to the teachings of Islam of course. The phenomenon in the current era is that many young people deviate from Islamic morals and ethics. The purpose of writing this article is to find out the concept of morals and ethics in Islam, the importance of moral and ethical integration in Islamic education and finally the implementation of moral and ethical integration in Islamic education. This writing method uses Library Resarch by collecting various sources of books, articles or other related sources. after that it will be analyzed descriptively and associated with the existing discussion topics. The concept of morals and ethics in Islam is an important aspect in the life of a Muslim. Integrating morals and ethics in Islamic education is very important because it will direct a learner in the intelligence of life and behavior. In addition, there are many positive impacts that a learner gets in running his life. Having a sense of responsibility, good character, and living a good life with fellow humans and God. Religion has a close relationship with morals and ethics. This relationship involves the influence of religion on the formation and understanding of moral values and ethical norms in human life. The implementation of moral and ethical integration in Islamic education can be done through curriculum development in institutions, interactive learning, Islamic character building. In its implementation requires cooperation from all parties related to students, teachers, parents and also the environment around students